The engagement of people with lived experiences in substance use research - Kim, Catherine (Frontiers in Public Health, 2025)
BackgroundPeople with lived experiences (PWLE) are underrepresented in research engagement, however their involvement can significantly boost the relevance and impact of research. Questions concerning the credibility and trustworthiness of PWLE researchers by traditional and positivist researchers have been identified. Having been associated with substance use of questionable legality and related substance use activities, PWLE researchers face stigma and are deemed to lack the trustworthiness that serious research entails. Current literature on PWLE found a dearth of knowledge on the definitions and conceptualizations of PWLE in research, which this paper attempts to partially address.MethodsIssues surrounding the trustworthiness of PWLE in substance use research were investigated, along with accounts of involving PWLE at different phases of the research process.FindingsPeople with lived experiences have been undervalued as researchers compared to other positivist counterparts despite advocating against marginalization and oppressive practices. They offer in-depth, meaningful contributions to research involving phenomena that they have experienced and were found to provide insights that other non-PWLE researchers overlooked. Moreover, engaging PWLE in research is not only beneficial for research processes and outcomes but is also empowering for PWLE themselves.ConclusionA guide to maintaining trustworthiness and a description of PWLE contributions to research processes are provided.